How do young innovative companies innovate? - Gabriele Pellegrino; Mariacristina Piva; Marco Vivarelli (Institute for the Study of Labor (IZA), 2009)
This paper discusses the determinants of product innovation in young innovative companies (YICs) by looking at in-house and external R&D and at the acquisition of external technology in embodied and disembodied components. These input-output relationships are tested on a sample of innovative Italian firms. A sample-selection approach is applied. Results show that in-house R&D is linked to the propensity to introduce product innovation both in mature firms and YICs; however, innovation intensity in the YICs is mainly dependent on embodied technical change from external sources, while - in contrast with the incumbent firms - in-house R&D does not play a significant role.
urn:nbn:de:101:1-2009082596
Keywords: O31; 650; R&D; product innovation; embodied technical change; CIS 3; sample selection; Innovation; Unternehmensgründung; Industrielle Forschung; Make or Buy; Wissenstransfer; Forschungskooperation; Italien